Tight- binding study of electronic band structure of anisotropic honeycomb lattice - maryam Hojatifar; Peyman Sahebsara (Journal of Optoelectronical Nanostructures, 2016)
The two-dimensional structure of graphene, consisting of an isotropic hexagonal lattice of carbon atoms, shows fascinating electronic properties, such as a gapless energy band and Dirac fermion behavior of electrons at fermi surface. Anisotropy can be induced in this structure by electrochemical pressure. In this article, by using tight-binding method, we review anisotropy effects in the electronic nanostructure of graphene in one direction. For this purpose, we just consider π states, which express electronic characteristics, and compare electronic band of π states with that of isotropic honeycomb lattice in graphene. As a result, by applying pressure or stretching in one direction, the gap will be created in the electronic band at the fermion surface, which can be useful for semiconducting nano devices. The isotropic graphene has a band structure with no energy gap. By applying electrochemical pressure in one direction, the translational symmetry can be broken, therefore an energy gap appears between the two bands.